A Message Without a Code? - Tom Conley (Studies in 20th & 21st Century Literature, 1981)
The photographic paradox is said to be that of a message without a code, a communication lacking a relay or gap essential to the process of communication. Tracing the recurrence of Barthes's definition in the essays included in Image/Music/Text and in La Chambre claire, this paper argues that Barthes's definition is platonic in its will to dematerialize the troubling — graphic — immediacy of the photograph. He writes of the image in order to flee its signature. As a function of media, his categories are written in order to be insufficient and inadequate; to maintain an ineluctable difference between language heard and letters seen; to protect an idiom of loss which the photograph disallows. The article studies the strategies of his definition in «The Photographic Paradox» as instrument of abstraction, opposes the notion of code, in an aural sense, to audio-visual markers of closed relay in advertising, and critiques the layout and order of La Chambre claire in respect to Barthes's ideology of absence.
Keywords: message without a code; photography; Barthe; Image/Music/Text; La Chambre claire; dematerialization; media; audio-visual markers; abstraction; ideology of absence